Contrasting tocol ratios associated with seed longevity in rice variety groups - Lee, Jae-Sung; Kwak, Jieun; Yoon, Mi-Ra; Lee, Jeom-Sig; Hay, Fiona R. (Cambridge University Press, 2017)
Vitamin E (tocols) is a key metabolite for efficient scavenging of lipid peroxy radicals that cause membrane breakdown during seed ageing. However, in rice, this hypothesis has been tested for very few lines only and without considering intraspecific variation in genomic structure. Here, we present a correlation study between tocols and seed longevity using a diverse rice panel. Seeds of 20 rice accessions held in the International Rice Genebank at the International Rice Research Institute, representing Aus, Basmati/Sadri, Indica, temperate Japonica and tropical Japonica variety groups, were used for tocols analysis (quantification of α-, β-, γ- and δ-tocopherol/tocotrienol by ultra-performance liquid chromatography) and storage experiments at 45°C and 10.9% seed moisture content. To examine the effects of DNA-haplotype on the phenotype, the 700 K high-density single-nucleotide polymorphism marker dataset was utilized. Both seed longevity (time for viability to fall to 50%; p50) and tocols content varied across variety groups related to the heterogeneity in the genetic architecture. Among eight types of tocol homologues, α-tocopherol and γ-tocotrienol were significantly correlated with p50 (negatively and positively, respectively). While temperate Japonica varieties were most abundant in α-tocopherol, Indica varieties recorded 1.3- to 1.7-fold higher γ-tocotrienol than those of other groups. We conclude that the specific ratio of tocol homologues rather than total tocols content plays an important role in the seed longevity mechanism.